Neo-Orientalisme dalam Islam Melayu: Analisis Komparatif atas Strategi Akomodasi, Negosiasi, dan Resistensi Epistemik dalam Pemikiran Intelektual Indonesia dan Malaysia - Fauzan Haviz; Nunu Burhanuddin (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
Neo-Orientalism, as a new form of epistemic colonialism, continues to shape the representation of Malay Islam in Indonesia and Malaysia through narratives of marginality, essentialism, and Western global discourse hegemony. This study conducts a comparative analysis of intellectual responses by key figures in both countries to this knowledge hegemony. In Indonesia, Nurcholish Madjid and Abdurrahman Wahid employed critical accommodation strategies by Islamizing values of democracy and pluralism. Azyumardi Azra engaged in epistemic negotiation by reconstructing historical networks of ulama to reject the “peripheral Islam” narrative. In Malaysia, Chandra Muzaffar negotiated critiques of Western bias in human rights discourse, while Syed Naquib al-Attas promoted radical epistemic resistance through the Islamization of knowledge based on adab and tawhid. Haedar Nashir in Indonesia rejected the “moderate vs radical” categorization as a neo-Orientalist project. The analysis reveals that Malay Islam is not anti-modernity but actively Islamizes modernity. Differences in strategies reflect national contexts, yet their synthesis forms an alternative civilization model that is tolerant and cosmopolitan. This research proposes a decolonization model for Malay Islamic knowledge that integrates accommodation, negotiation, and resistance for an independent scholarly future. (198 words)